MATEMATIKA BOYÍNSHA AUDITORIYALÍQ SABAQLARDA TALABALARDÍŃ ÓZ BETINSHE JUMÍSLARÍN SHÓLKEMLESTIRIW - Jańabergenova, A. (SCIENCE and SOCIETY, 2018)
The article contains interesting ideas how to use maximally mathematical skills at lessons in the classroom and in independent work of students of higher educational institutions.
Keywords: independent work; tasks; lesson; types of lesson; Mathematics; auditorium; professional competency